Effect of environmental enrichment and herbal compound supplementation on physiological stress indicators (chromogranin A, cortisol and tumour necrosis factor-α) in growing pigs. (8th December 2016) - Casal, N.; Manteca, X.; Escribano, D.; Cerón, J. J.; Fàbrega, E.
Abstract : Stress response induces physiological, behavioural, immunological and biochemical changes that directly affect health and well-being. Provision of environmental enrichment and herbal compounds may reduce stress in current commercial pig husbandry systems. The aim of this study was to evaluate the effect of providing different environmental enrichment materials (EE) and a herbal compound (HC) on physiological indicators of acute and chronic stress in growing pigs (salivary cortisol and chromogranin A (CgA), hair cortisol and tumour necrosis factor- α (TNF- α )). Salivary cortisol and CgA have been reported as biomarkers basically of acute stress, whereas hair cortisol and TNF- α have been more related to chronic stress. For this purpose, eight groups of seven pigs each (14 pigs/treatment, 56 pigs in total) were used: (a) two EE groups, (b) two groups supplemented with HC, (c) two groups provided both with EE and HC and (d) two control groups. Samples of hair, saliva and blood were taken to measure cortisol (in hair and saliva), CgA (in saliva) and TNF- α (in blood) at three different times: before starting the experiment (T0), and after 1 (T1) or 2 months (T2) of providing the materials and herbal compound. No differences were found at T0 in salivary or hair cortisol, CgA or TNF- α, whilst at T2, the control group showed significant increased concentrations of CgA and hair cortisol, when compared with the rest of the treatments ( P <0.001). These differences were significant at T1 only for CgA ( P <0.001). Furthermore, an overall correlation was reported between hair cortisol and salivary CgA ( r =0.48, P <0.001). These results support that providing enrichment material or an herbal compound may reduce stress in growing pigs. Furthermore, the results support that hair cortisol and CgA may be proper non-invasive tools to detect stress, specially associated with factors of chronic exposure.